2016
DOI: 10.1038/nrdp.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroids

Abstract: Uterine fibroids (also known as leiomyomas or myomas) are common clonal neoplasms of the uterus. Fibroids have both smooth muscle and fibroblast components, in addition to a substantial amount of fibrous extracellular matrix, which all contribute to the pathogenetic process. Fibroids are extremely heterogeneous in their pathophysiology, size, location and clinical symptomatology. They are also a part of a range of disease in which some variants have facets of malignant behaviour but overall are benign. Risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
352
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(392 citation statements)
references
References 172 publications
3
352
0
4
Order By: Relevance
“…Uterine leiomyomata (LMs) or fibroids are benign tumors of myometrium (MM), which occur in women of reproductive age with the cumulative incidence of approximately 70% (13). Recent comprehensive genome analyses identified at least 4 major LM subtypes with unique genetic alterations (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Uterine leiomyomata (LMs) or fibroids are benign tumors of myometrium (MM), which occur in women of reproductive age with the cumulative incidence of approximately 70% (13). Recent comprehensive genome analyses identified at least 4 major LM subtypes with unique genetic alterations (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fibroid tumor size was significantly decreased in response to progesterone withdrawal using the PR antagonist mifepristone (RU486) (80,81). As a result of these and other studies, several selective progesterone receptor modulators (SPRMs) have been shown in clinical trials to inhibit UF growth (49,50,8287). …”
Section: Pathogenesis Of Uterine Fibroidsmentioning
confidence: 89%
“…Most of uterine fibroid cases are sporadic in nature, however few rare familial syndromes are associated with development of UFs. In these syndromes, genetic alterations occur in the FH , COL4A5 and COL4A6 genes (49). In sporadic tumors, several recurrent genetic aberrations have been identified, including deletions in 7q, trisomy of chromosome 12, reciprocal translocation of chromosome 12, and monosomy of chromosome 22, among others (5052).…”
Section: Pathogenesis Of Uterine Fibroidsmentioning
confidence: 99%
“…Uterine fibroids (UFs) are common benign tumors of the female genital tract. They are diagnosed in almost one-quarter of women of reproductive age [1]. UFs may cause numerous clinical symptoms, including prolonged or heavy menstrual bleeding, pelvic pressure symptoms or pain, infertility and obstetric complications, but are mostly asymptomatic [1].…”
Section: Introductionmentioning
confidence: 99%